2014
DOI: 10.1136/tobaccocontrol-2014-051683
|View full text |Cite
|
Sign up to set email alerts
|

No lasting effects of plain packaging on cigarette pack retrieval time in small Australian retail outlets

Abstract: To cite Bayly M, Scollo M, Wakefield M. Tob Control 2015;24:e108-e109. Figure 1 Adjusted average pack retrieval duration with 95% CIs, by month, controlling for city, area SES and store type. Research lettere108

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…This study was part of a larger exercise that aimed to collect information about transaction times 24 25 and willingness to sell illicit tobacco, 7 which necessitated unobtrusive data collection. Each month, fieldworkers entered the stores under the guise of a regular customer, and discretely observed the contents of the price board.…”
Section: Methodsmentioning
confidence: 99%
“…This study was part of a larger exercise that aimed to collect information about transaction times 24 25 and willingness to sell illicit tobacco, 7 which necessitated unobtrusive data collection. Each month, fieldworkers entered the stores under the guise of a regular customer, and discretely observed the contents of the price board.…”
Section: Methodsmentioning
confidence: 99%
“…As indicated by the data showing the effectiveness of positioning health warnings on the upper part of the cigarette pack, scientific investigation plays a key role in overturning unsubstantiated opinions 24,35 . When plain packaging was implemented in Australia, the tobacco industry argued that this would lead to longer transaction times and customer frustration 36 . However, no increases in pack transaction times were observed (Carter et al 37 , Bayly et al 36 , and Wakefield et al 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…When plain packaging was implemented in Australia, the tobacco industry argued that this would lead to longer transaction times and customer frustration 36 . However, no increases in pack transaction times were observed (Carter et al 37 , Bayly et al 36 , and Wakefield et al 38 ). Additionally, tobacco companies argued that cigarette advertising and display at the point-of-sale target only adult smokers 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Scientific evidence has shown that the implementation of plain packaging reduces smoking prevalence [16], increases thoughts about quitting and calls to quit lines [17,18], reduces brand awareness, attractiveness and appeal of the package [19][20][21], and increases the salience and effectiveness of health warnings among adolescents [22]. Moreover, despite claims of the opposite, the implementation of plain packaging does not impact illicit trade or product retrieval time [23][24][25].…”
Section: Plain Packaging Workmentioning
confidence: 99%